Digital Financing Business Models for MSMEs in Indonesia: Effect on Financial Access, Productivity, and Job Creation toward SDG 8 - Adji Dwi Satya; Cupian; Yudi Ahmad Faisal (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
This study examines the role of digital financing business models in improving financial access and supporting MSME performance in Indonesia, aligned with SDG 8 goals of increasing productivity and job creation. Using a quantitative approach, the study surveyed 120 MSME owners from the Jakpreneur program in Jakarta. Quantitative data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results show that a well-designed digital financing business model significantly increases MSMEs’ use of digital financing platforms, which in turn improves financial access. Financial access has a strong positive effect on productivity and facilitates job creation, primarily through better employee welfare and capacity expansion. These findings highlight that digital financing not only enhances access to capital but also drives operational efficiency and sustainable business growth. The study contributes to the understanding of how digital financial solutions can act as a catalyst for inclusive economic development and provides insights for platform providers, policymakers, and future researchers to optimize their role in empowering MSMEs.